Kegagalan Permukaan Kontak Rail dan Wheel pada Overhead Travelling Crane - Azhar; Ajinar; Zainuddin (Yayasan Kawanad, 2022)
For the sake of the smooth process of cement production, it is necessary to maintain each component of the production. One of the tools that play an important role in the maintenance and production of cement is the Overhead Traveling Crane, which is a combination of a separate lifting mechanism with a frame to lift and move loads that can be hung freely or attached to the crane itself. The problems that arise in the Overhead Traveling Crane include the reverse direction of the motor rotation due to an error in the motor connection, the motor cannot start due to a disconnected power supply, the occurrence of bending (curving) on ​​the girder due to lifting operations that exceed the maximum capacity which can also accelerate service life. of the girder, wear on the wheel due to high workload during operation. Due to the need for very long use, periodic maintenance is needed so that it can be in normal condition for a long time. The main parts that support the overall weight of the crane are rails and wheels. This journal discusses the analysis of failures that occur due to contact between rails and wheels that occur in a cement factory. Failure analysis is done by testing the hardness of both the wheel and the rely which is considered to have failed or is no longer suitable for use. Then review the results of direct field observations with data from hardness tests and literature studies related to wheels and rails. after that it was concluded that the company considered for the procurement of rails and wheels. The conclusion obtained is that the hardness value on the rail is lower than on the wheel. Resulting in failure of the rail so that the rail must be replaced.